Diamond Nanophotonic Circuits Functionalized by Dip‐pen Nanolithography. Issue 3 (13th October 2014) - Rath, Patrik; Hirtz, Michael; Lewes‐Malandrakis, Georgia; Brink, Dietmar; Nebel, Christoph; Pernice, Wolfram H. P.
<x xml:space="preserve">Abstract</x> Nanophotonic circuits based on polished diamond thin films are prepared. These circuits cover a wide wavelength range across the entire visible spectrum. Integrated devices are surface functionalized site‐specifically and in parallel using dip‐pen nanolithography with a minimum linewidth of 100 nm. Multicolor fluorescence is coupled into the underlying photonic network using microring resonators and grating structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>